2016
DOI: 10.1038/ajg.2016.485
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Advancing Adoption of Frailty to Improve the Care of Patients with Cirrhosis: Time for a Consensus on a Frailty Index

Abstract: Frailty is a key determinant of outcomes in patients with cirrhosis. Two papers in this issue of the American Journal of Gastroenterology advance our understanding of the mechanism by which frailty impacts mortality -by increasing the risk of hospitalization for liver-related complications. We now have overwhelming justification to incorporate frailty into clinical practice, but this should be done in a systematic way to foster multi-center collaboration to accelerate research in this field. It's time for cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…The lack of consensus for a feasible, reliable, and objective test of physical frailty for clinical use in liver transplantation has limited the application of the diagnosis of the frailty phenotype in clinical hepatology practice . We developed the LFI specifically for patients with cirrhosis using a parsimonious battery of tests that have been incorporated into composite frailty indices in the field of geriatrics for decades .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of consensus for a feasible, reliable, and objective test of physical frailty for clinical use in liver transplantation has limited the application of the diagnosis of the frailty phenotype in clinical hepatology practice . We developed the LFI specifically for patients with cirrhosis using a parsimonious battery of tests that have been incorporated into composite frailty indices in the field of geriatrics for decades .…”
Section: Discussionmentioning
confidence: 99%
“…transplantation has limited the application of the diagnosis of the frailty phenotype in clinical hepatology practice. (10) We developed the LFI specifically for patients with cirrhosis using a parsimonious battery of tests that have been incorporated into composite frailty indices in the field of geriatrics for decades. (1,2) Thus far, we have demonstrated that the LFI improves risk prediction of wait-list mortality over the MELD-Na alone, (3) can enhance subjective clinician assessments of a patient's global health status, (6) and is strongly associated with robustness of physical function after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…3 While several studies have investigated frailty 1,4 or aspects of frailty (eg, cardiopulmonary fitness, 5,6 disability, 7,8 ) in the pre–liver transplant setting, these tools have characteristics that have hampered efforts to fully understand if, how, and when frailty reverses after liver transplantation. For example, tools such as the Fried Frailty Index or Activities of Daily Living scale are subjective and scored on a noncontinuous scale, making them insensitive to subtle changes over time; cardiopulmonary exercise testing is technically challenging to administer, limiting the number of patients who are able to undergo repeat posttransplant testing.…”
Section: | Introductionmentioning
confidence: 99%
“…Such information is crucial to informing discussions with patients and caregivers about what to expect after liver transplantation and guiding prognosis regarding quality of life.One of the major barriers to investigating recovery from physical frailty after liver transplantation has been the frailty measurement tools themselves. 3 While several studies have investigated frailty 1,4 or aspects of frailty (eg, cardiopulmonary fitness, 5,6 disability, 7,8 ) in the pre-liver transplant setting, these tools have characteristics that have hampered efforts to fully understand if, how, and when frailty reverses after liver transplantation. For example, tools such as the Fried Frailty Index or Activities of Daily Living scale are subjective and scored on a noncontinuous scale, making them insensitive to Frailty is prevalent in liver transplant candidates, but little is known of what happens to frailty after liver transplantation.…”
mentioning
confidence: 99%
“…23 The biologic construction of physical frailty, originally developed in the field of geriatrics, has been shown to capture the effects of end-stage liver failure in adults ("relative chronologic youth") and predict post-transplant outcomes and morbidity. [24][25][26] The concept of frailty has been extended to children, with a recent study demonstrating feasibility of testing for the five domains of the Fried Frailty Phenotype in a multicenter cohort of children between the ages of 5 and 18 years with chronic liver disease, with 46% meeting the criteria for frailty at a single baseline assessment. 27 However, the majority of wait listed children are under the age of 5 years, and thereby too young to undergo functional or performance-based (frailty) testing before time of LT.…”
Section: Enhancing Risk Stratification Of Patients On the Wait Listmentioning
confidence: 99%